ChemInform Abstract: Rh‐Catalyzed Construction of Quinolin‐2(1H)‐ones via C—H Bond Activation of Simple Anilines with CO and Alkynes. Issue 3 (29th December 2015) - Li, Xinyao; Li, Xinwei; Jiao, Ning
Abstract: A novel procedure is elaborated for the synthesis of quinolin‐2(1H)‐ones (IV), (VI), and (VIII) by Rh‐catalyzed reaction of N‐alkylanilines with CO and symmetrical alkynes in the presence of Cu(O‐Ac)2 as an oxidant.